2013
DOI: 10.4104/pcrj.2013.00017
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients preferring once-daily controller therapy for asthma and COPD: a retrospective cohort study

Abstract: Background: Patient preference is an important factor when choosing an inhaler device for asthma or chronic obstructive pulmonary disease (COPD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…Several single results showed better adherence in people with a family history of asthma [71], asthma onset at younger age [58], lower impulsivity [62] and high literacy [80]. Other single findings suggested that more adherent people attribute their asthma more to external factors [41], believe that God is less in control of their health and attribute more control to physicians [73], perceive themselves less vulnerable to side-effects, report higher intention to use inhalers [72], have better inhaler use skills [79], are more satisfied with the device [70], prefer to use inhalers rather than pills [32], have no preferences regarding daily inhaler dosage [75], believe more strongly in participating actively in care [36], and report no symptom improvement due to herbal drugs [52].…”
Section: Nrmentioning
confidence: 99%
“…Several single results showed better adherence in people with a family history of asthma [71], asthma onset at younger age [58], lower impulsivity [62] and high literacy [80]. Other single findings suggested that more adherent people attribute their asthma more to external factors [41], believe that God is less in control of their health and attribute more control to physicians [73], perceive themselves less vulnerable to side-effects, report higher intention to use inhalers [72], have better inhaler use skills [79], are more satisfied with the device [70], prefer to use inhalers rather than pills [32], have no preferences regarding daily inhaler dosage [75], believe more strongly in participating actively in care [36], and report no symptom improvement due to herbal drugs [52].…”
Section: Nrmentioning
confidence: 99%
“…It was reported as an ideal factor of treatment by a similar proportion of participants with asthma in the first phase of the study (n ¼ 6/39 [15.4%]]) [1] to those who rated this attribute as 'extremely important to me' in the current phase of the study (n ¼ 30/152 [19.7%]). The variable nature of asthma symptoms may at least partially explain why individuals with asthma and poor adherence have reported a preference for once-daily treatment [36]; patients with asthma prescribed oncedaily treatment had approximately 20% higher levels of adherence than those prescribed therapies needed twice or more daily [37]. Once-daily treatments may be preferred by patients with asthma who consider that they are too busy to take medication more frequently [24,38].…”
Section: Discussionmentioning
confidence: 99%
“…on treatment adherence in patients with asthma, mean adherence rates were greater with a once-daily regimen compared with twice daily [115]. In a survey of patients with COPD, those who reported low adherence were more likely to prefer once-daily medication than were those with good adherence; this preference was found to be associated with a high self-perceived need for controller medication [116], indicating the importance of tailoring treatment decisions to the individual patient's needs and preferences. Persistence with inhaled medications for COPD is also directly related to the daily frequency of administration [117].…”
Section: Adherence/persistencementioning
confidence: 91%
“…The relationship between a simple dosing regimen and improved adherence has been reasonably well studied in asthma and COPD [115,116,120], and using a medication dosed once daily should help in addressing the problem of non-adherence. A patient's perception of benefit when restarting a medication or changing to a faster-onset one may be useful to the treating physician in improving the management of a poorly adherent patient.…”
Section: Remaining Questions and Future Researchmentioning
confidence: 99%